Camden active spaces: Does the construction of active school playgrounds influence children's physical activity levels? A longitudinal quasi-experiment protocol. Issue 8 (13th August 2014) - Smith, Lee; Kipps, Courtney; Aggio, Daniel; Fox, Paul; Robinson, Nigel; Trend, Verena; Munnery, Suzie; Kelly, Barry; Hamer, Mark
Abstract : Introduction: Physical activity is essential for every facet of children's health. However, physical activity levels in British children are low. The school environment is a promising setting to increase children's physical activity but limited empirical evidence exists on how a change in the outdoor physical school environment influences physical activity behaviour. The London Borough of Camden is redesigning seven existing school playgrounds to engage children to become more physically active. The primary aim of this project is to evaluate the impact of the redesigned playgrounds on children's physical activity, well-being and physical function/fitness. Method and analysis: This project will use a longitudinal quasi-experimental design. Seven experimental schools and one control school will take part. One baseline data collection session and two follow-ups will be carried out. Between baseline and follow-up, the experimental school playgrounds will be redesigned. At baseline, a series of fitness tests, anthropometric and questionnaire measurements, and 7-day objective physical activity monitoring (Actigraph accelerometer) will be carried out on children (aged 5–16 years). This will be repeated at follow-up. Changes in overall physical activity levels and levels during different times of the day (eg, school breaks) will be examined. Multilevel regression modelling will be used to analyse the data. Ethics and dissemination: The results of this study will be disseminated through peer-review publications and scientific presentations. Ethical approval was obtained through the University College London Research Ethics Committee (Reference number: 4400/002).